A proteção socioambiental e a responsabilidade penal pelo uso indevido da água - Silva, Tarinê Cortina Poeta Castilho da (2023)
Criminal law is an appropriate legal instrument for preventing environmental damage to water resources, given that water is a vital element found in nature and is part of almost every type of material in the natural and artificial environment. The criminal system is designed to protect water resources in a specific way, to restrain and punish the perpetrator of the crime, given the legal nature of criminal law, i.e. its preventive nature in relation to crime. However, when looking at legal entities, when it comes to environmental crimes and infractions, although they are criminally liable for the damage, the effectiveness of criminal law will only be effective in conjunction with civil liability. The methodology used in this study is hypothetical deductive combined with the empirical method due to the data collection corresponding to the analysis of more than 11 thousand environmental infractions that occurred between the years 2016 to 2021 in the state of Paraná, as well as all the water environmental crimes that passed through the Court of Justice of the State of Paraná from 1984 to 2021. This showed that, quantitatively, individuals cause more environmental damage, but when ranking the 10 (ten) biggest environmental offenders, legal entities occupy 70% of the positions. After analyzing the data presented, it is possible to see that in the administrative sphere there are constant recidivism of offenders, as well as an exorbitant number of infractions compared to environmental crimes, thus demonstrating the need for stricter legislation, both in terms of greater penalties and civil liability of equal weight, in order to prevent not only specific recidivism, but also environmental damage from occurring.